PENGARUH STRESKERJA, KONFLIK KERJA, LINGKUNGANKERJA DAN KOMPENSASI TERHADAPKINERJAKARYAWAN DENGAN PEMBERIANKOMPENSASI SEBAGAI VARIABEL MODERASI PADABAKPIAPATHOK25 YOGYAKARTA - Prita Sari Dewi; Juarini Juarini; Siti Hamidah (Jurnal Dinamika Sosial Ekonomi, 2018)
The aim of this study was to analyze the level of work stress, work conflict, work environment, compensation, and employee performance as well as to analyze the effect of work stress, work conflict, and work environment on the employee performance in Bakpia Pathok 25 Yogyakarta by using compensation as a moderator variable. The method used in this research was a case study. The selection of respondents used census methods with a total of 81 permanent employees. Data were collected by observation, documentary, and interview. Methods of data analysis were descriptive analysis, tabulation, and moderated regression analysis (MRA) with multiple linear models. The results showed that there was moderate level of workstress, high workconflictlevel, moderate work environmentlevel, hig compensation level, and high employee performance level. It was concluded that work stress and work environment affected the employee performance while with compensation, work conflict affected the employee performance. Keywords: workstress, work conflict, work environment, compensation, moderatorvariable, employeeperformance